Training children with autism in Computer Science through inclusive and distance learning: A descriptive and explanatory case study - Salgarayeva, Gulnaz; Sabit, Botakoz (Jurnal Cakrawala Pendidikan, 2026)
In inclusive education, information technology and traditional teaching methods significantly impact the development of child’s intelligence, motor skills, and visual and motor analyzers. In this regard, the role of Computer Science (CS) in school is special. In this context, children with autism spectrum disorders (ASD) often benefit from simplified curricula and technological tools, such as distance learning tools, which have gained popularity after COVID-19. This study investigated the pedagogical strategies and outcomes of CS distance learning for children with ASD in inclusive education and determined its effectiveness. This descriptive and explanatory case study focuses on the practice of distance learning process (effectiveness, impact, barriers, problems, etc.). In the context of inclusive education, students with ASD in CS could perform computer tasks remotely along with normal children, and their academic activity increased.  While studying remotely, they also encountered several difficulties, as a result of which they tried to solve the problems themselves. It was shown that children with ASD can be taught CS remotely and its advantages are demonstrated. The study indicates that teaching children with ASD to learn CS in inclusive education and distance learning settings is feasible and effective. The results suggest that children with ASD can make significant progress in their computational skills when provided with an environment that meets their learning needs, whether through flexible applications, individualized support, or virtual classroom structures.